Prevalence of metabolic syndrome and its associated factors in Chinese patients with ankylosing spondylitis [Corrigendum] - Liu M (Dove Medical Press, 2019)
Liu M, Huang Y, Huang Z, et al. Diabetes Metab Syndr Obes. 2019;12:477–484. On page 478, Under Patients and methods section, Clinical evaluation and laboratory tests subheading, the sentence should read from “According to the latest Chinese overweight/obesity medical nutrition treatment expert consensus (2016),16 overweight is defined as 24 kg/m2 ≤ BMI ☐28 kg/m2 and obesity is defined as BMI ≥28 kg/m2.” to “According to the latest Chinese overweight/obesity medical nutrition treatment expert consensus (2016),16 overweight is defined as 24 kg/m2 ≤ BMI <28 kg/m2 and obesity is defined as BMI ≥28 kg/m2.” The correct correspondence address should read as follows: Department of Rheumatology and Immunology, Guangdong Second Provincial General Hospital, No 466 Xingangzhong Road, Haizhu District, Guangzhou, Guangdong 510317, People’s Republic of China.Read the original article.